Bile reflux and bile acids in the progression of gastric intestinal metaplasia. Issue 14 (20th July 2022) - Qu, Xiaodong; Shi, Yongquan
Abstract : Abstract: Gastric intestinal metaplasia (GIM) is a precancerous lesion of gastric cancer (GC) and is considered an irreversible point of progression for GC. Helicobacter pylori infection can cause GIM, but its eradication still does not reverse the process. Bile reflux is also a pathogenic factor in GIM and can continuously irritate the gastric mucosa, and bile acids in refluxed fluid have been widely reported to be associated with GIM. This paper reviews in detail the relationship between bile reflux and GIM and the mechanisms by which bile acids induce GIM.